2020
DOI: 10.1177/2516043520914215
|View full text |Cite
|
Sign up to set email alerts
|

The cost-effectiveness of sub-epidermal moisture scanning to assess pressure injury risk in U.S. health systems

Abstract: Objective Hospital-acquired pressure injuries harm over 2.5 million patients at a U.S. cost of $26.8 billion. Sub-epidermal moisture scanning technology supports clinicians to anatomically identify locations at-risk of developing hospital-acquired pressure injuries. Our objective was to evaluate the cost-effectiveness of adopting sub-epidermal moisture scanners in comparison to existing hospital-acquired pressure injury prevention guidelines structured around subjective risk assessments. Methods A Markov cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 24 publications
0
16
0
3
Order By: Relevance
“…In the aggregate, results from this study in combination with laboratory studies, 14 inter-operator reliability studies, 19 damaged and healthy tissue studies, 26,49 longitudinal assessments 18 and other SEM studies 15,29,31,32,35,[50][51][52] through different tests of SEM have repeatedly shown that SEM is a predictor and a reliable indicator of the early onset of pressure-induced skin and tissue damage. Furthermore, a health economics analysis performed by Padula et al (2020), shows that prevention using the SEM test is cost-saving and is dominant in quality interventions when compared to the current standard of PI/PU care. 53 Certainly, prevention keeps the skin intact and the costs associated with treating broken skin and open wounds are intensive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the aggregate, results from this study in combination with laboratory studies, 14 inter-operator reliability studies, 19 damaged and healthy tissue studies, 26,49 longitudinal assessments 18 and other SEM studies 15,29,31,32,35,[50][51][52] through different tests of SEM have repeatedly shown that SEM is a predictor and a reliable indicator of the early onset of pressure-induced skin and tissue damage. Furthermore, a health economics analysis performed by Padula et al (2020), shows that prevention using the SEM test is cost-saving and is dominant in quality interventions when compared to the current standard of PI/PU care. 53 Certainly, prevention keeps the skin intact and the costs associated with treating broken skin and open wounds are intensive.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a health economics analysis performed by Padula et al (2020), shows that prevention using the SEM test is cost-saving and is dominant in quality interventions when compared to the current standard of PI/PU care. 53 Certainly, prevention keeps the skin intact and the costs associated with treating broken skin and open wounds are intensive.…”
Section: Discussionmentioning
confidence: 99%
“…Deploying the SEM Scanner as an adjunct to routine PI care pathways results in significant PI incidence reductions. In multiple care settings, PI-related hospitalizations and subsequent high PI treatment costs are avoided resulting in the SEM Scanner being clinically more effective and less expensive than the current standard of care [50]. (QEF) [41].…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…Additional economic models indicate using the device in routine clinical practice as a dominant quality intervention, as it is more effective and less costly than the current SoC. In multiple care settings, highest per‐patient cost savings are realised due to large treatment costs avoided from later stage PI/PUs and PI/PU‐related hospitalisation (Padula et al, 2020).…”
Section: Discussionmentioning
confidence: 99%